A Note on the "One Case per Stagger Position" Character of Common Multiple-Baseline Intervention Designs. (3rd April 2019) - Levin, Joel R.; Gafurov, Boris S.
ABSTRACT: Purpose : To overcome the constraint of common multiple-baseline designs that only one case per stagger position is permitted. Methods : Three alternative strategies for assigning more than one case to each stagger position are examined. Results : The three recommended strategies achieve the objective while maintaining the study's internal and statistical-conclusion validities. Conclusions : ExPRT, a freely available Excel-based randomization-test package, can be used to assist in both the design and statistical analysis associated with each of the strategies.